Penggunaan Berbagai Sumber Karbohidrat Terlarut Air untuk Meningkatkan Kualitas Silase Daun Rami - Despal Despal; I G Permana; S N Safarina; A J Tatra (Faculty of Animal Science, Bogor Agricultural University, 2011)
Quality improvement of ramie leaves silage by the addition of water soluble carbohydrates (WSC) sources as many as 20% W/W fresh substance (FS) prior to 42 days of ensiling time was conducted in two experiments. First experiment examined three carbohydrate sources (cassava meal, pollard and coarse grinding corn) for their capacities to improve physical (color, odor, texture and spoilage), fermentative (pH, protein degradation, organic acid profiles), and utilities characteristics of the silages for ruminants (rumen fermentabilities and digestibilities) in vitro. The silages had bright greenish brown of color, lactic acid odor, and firm textures, categorized as highly fermentable and digestible feeds (dry matter digestibility >72%). Compare to other additives, cassava meal produced better silage. However, high butyric acid and protein degradation proportions in the silage were not seem in line to these data. Coarse grinding corn failed to do its function therefore produced poor silage quality. Second experiment was designed to confirm the previous results. Five carbohydrate sources (cassava meal, pollard, fine grinding corn, rice bran, and cassava extract meal) of the same functions were examined. The results confirmed that cassava meal produced very good ramie leave silages (Fleigh number >80) while the others produced quite good ramie leaves silage qualities (Fleigh number 40-60). All additives used in the second experiment successed to serve their functions in improving ramie leave silage qualities.